+0  
 
0
375
2
avatar+7002 

Evaluate \(\displaystyle \int\dfrac{\sin x}{\sin x + \cos x}\mathtt{d}x\)

MaxWong  Jun 3, 2017
 #1
avatar
+1

Take the integral:
 integral(sin(x))/(sin(x) + cos(x)) dx


Multiply numerator and denominator of (sin(x))/(sin(x) + cos(x)) by csc^3(x):
 = integral(csc^2(x))/(csc^2(x) + cot(x) csc^2(x)) dx


Prepare to substitute u = cot(x). Rewrite (csc^2(x))/(csc^2(x) + cot(x) csc^2(x)) using csc^2(x) = cot^2(x) + 1:
 = integral(csc^2(x))/(cot^3(x) + cot^2(x) + cot(x) + 1) dx
For the integrand (csc^2(x))/(cot^3(x) + cot^2(x) + cot(x) + 1), substitute u = cot(x) and du = -csc^2(x) dx:
 = integral-1/(u^3 + u^2 + u + 1) du


Factor out constants:
 = - integral1/(u^3 + u^2 + u + 1) du


For the integrand 1/(u^3 + u^2 + u + 1), use partial fractions:
 = - integral((1 - u)/(2 (u^2 + 1)) + 1/(2 (u + 1))) du


Integrate the sum term by term and factor out constants:
 = -1/2 integral(1 - u)/(u^2 + 1) du - 1/2 integral1/(u + 1) du


Expanding the integrand (1 - u)/(u^2 + 1) gives 1/(u^2 + 1) - u/(u^2 + 1):
 = -1/2 integral(1/(u^2 + 1) - u/(u^2 + 1)) du - 1/2 integral1/(u + 1) du


Integrate the sum term by term and factor out constants:
 = 1/2 integral u/(u^2 + 1) du - 1/2 integral1/(u^2 + 1) du - 1/2 integral1/(u + 1) du


For the integrand u/(u^2 + 1), substitute s = u^2 + 1 and ds = 2 u du:
 = 1/4 integral1/s ds - 1/2 integral1/(u^2 + 1) du - 1/2 integral1/(u + 1) du
The integral of 1/s is log(s):
 = (log(s))/4 - 1/2 integral1/(u^2 + 1) du - 1/2 integral1/(u + 1) du


The integral of 1/(u^2 + 1) is tan^(-1)(u):
 = -1/2 tan^(-1)(u) + (log(s))/4 - 1/2 integral1/(u + 1) du
For the integrand 1/(u + 1), substitute p = u + 1 and dp = du:
 = -1/2 tan^(-1)(u) + (log(s))/4 - 1/2 integral1/p dp


The integral of 1/p is log(p):
 = -(log(p))/2 + (log(s))/4 - 1/2 tan^(-1)(u) + constant
Substitute back for p = u + 1:


 = (log(s))/4 - 1/2 log(u + 1) - 1/2 tan^(-1)(u) + constant
Substitute back for s = u^2 + 1:
 = 1/4 log(u^2 + 1) - 1/2 log(u + 1) - 1/2 tan^(-1)(u) + constant


Substitute back for u = cot(x):
 = -1/2 log(cot(x) + 1) - 1/2 tan^(-1)(cot(x)) + 1/4 log(csc^2(x)) + constant
Factor the answer a different way:
 = 1/4 (-2 log(cot(x) + 1) - 2 tan^(-1)(cot(x)) + log(csc^2(x))) + constant
Which is equivalent for restricted x values to:
Answer: | = 1/2 (x - log(sin(x) + cos(x))) + constant

 

Sorry Max: I'm too old to learn LaTex! I hope you can follow it.

Guest Jun 3, 2017
 #2
avatar+7002 
+1

Not a problem at all... :D 

I can follow it :)

Thank you for helping :D

MaxWong  Jun 3, 2017
edited by MaxWong  Jun 3, 2017

7 Online Users

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.